A profile of garment export merchandisers in selected buying offices - Brillantes, Goldmina Hernandez; Dizon, Angelita Mendoza (2000.)
This descriptive study was an attempt to develop at profile of some garment export merchandisers in selected buying offices in Metro Manila to provide basic information on garment export merchandising in buying offices that would help job applicants. Data were gathered from 25 merchandisers and seven personnel managers using two sets of questionnaires. Analysis and interpretation of the results revealed that there are personal, educational, and work-experience requirements that are essential upon entering a career in merchandising in buying offices. Understanding the merchandisers' duties and responsibilities as well as the advantages and disadvantages of a career in merchandising are also important to help prepare aspiring students are also included to aid students in matching his or her expectations to a career in merchandising. Based on the results of the study, duties and responsibilities of garment export merchandisers in buying offices vary depending on the size of the company. Information on the staffing practices as described by the personnel managers provided insights on the general idea of what to expect in applying for a merchandising position in buying offices. The buying offices included in this study practice the staffing of recruitment, selection, orientation, wage and salary administration, performance appraisal, and training and development. Only manpower planning are being practiced by some of the buying offices. Students and graduates interested in garment export merchandising are suggested to review the required qualifications of a garment export merchandisers that will help them prepare for the job opportunities in garment export merchandising are also suggested to review their programs to help prepare their students for the jobs in garment export buying offices. Buying offices are recommended to consider planning an effective staffing process to reap the benefits of attracting the most qualified applicants, lessening employee turnover, increasing productivity, etc.
Thesis (BS Clothing Technology)--University of the Philippines Diliman.
Keywords: Clothing trade -- Philippines -- Employees